PEMBERIAN GRASI OLEH PRESIDEN BAGI TERPIDANA ANTASARI AZHAR - Bagus Teguh Santoso (universitas islam darul ulum lamongan, 2017)
Clemency and rehabilitation as the pardoning belong to the President’s prerogatives based on the attributie and discretion authority in consideration to endorse or to reject them. In the implementation of the prerogatives of the Presidential Decree (beschikking), the President should impose it wisely (guided by Principles of Algemene Beginselen Van Behoerlijk Bestuur) and by the concept of law (rechtmatigeheid). But in fact, politically there was “abuse of power” (detournement de povoir) and as if it were the President’s prerogatives in the field of discretion. It can be seen from the endorsement of Antasari Azhar clemency through the Presidential Decree No. 1 / G / 2017 dated on January 16, Th 2017, whereas in Antasari Azhar previous application for the clemency was rejected by the President pursuant to the Presidential Decree No.27 / G / 2015 dated on 27 July, Th 2015. As we all know the clemency application may strictly be purposed merely (1) onces (lex stricta, lex scripta, lex certa) as stipulated in Article 2 paragraph (3) of the Act No. 22 of 2002 as amended by the Act No. 5 of 2010 about clemency.